A Technology Training Program to Alleviate Social Isolation and Loneliness Among Homebound Older Adults: A Community Case Study - Jiménez, Frances N.; Brazier, Joan F.; Davoodi, Natalie M.; Florence, L. Carter; Thomas, Kali S.; Gadbois, Emily A. (Frontiers in Public Health, 2021)
Despite substantial evidence of the negative health consequences of social isolation and loneliness and the outsized impact on older adults, evidence on which interventions are most effective in alleviating social isolation and loneliness is inconclusive. Further complicating the translation of evidence into practice is the lack of studies assessing implementation and scalability considerations for socialization programs delivered by community-based organizations (CBOs). Our primary objective was to describe the implementation barriers, facilitators, and lessons learned from an information and communication technology (ICT) training program aimed at reducing social isolation and loneliness for homebound older adults in a home-delivered meals program. Participants received in-home, one-on-one ICT training lessons delivered by volunteers over a 14-week period with the goal of increasing social technology use. To assess implementation facilitators and barriers, twenty-three interviews were conducted with program staff (n=2), volunteers (n=3), and participants (n=18). Transcripts were analyzed using thematic analysis. Aspects that facilitated implementation included the organization’s existing relationship with clientele, an established infrastructure to deliver community-based interventions, alignment of intervention goals with broader organizational aims, and funding to support dedicated program staff. Challenges to implementation included significant program staff time and resources, coordinating data sharing efforts across multiple project partners, participant and volunteer recruitment, and interruptions due to COVID-19. Implications of these facilitators and barriers for scalability of community-based ICT training interventions for older adults are described. Lessons learned include identifying successful participant and volunteer recruitment strategies based on organizational capacity and existing recruitment avenues; using a targeted approach to identify potential participants; incorporating flexibility into intervention design when working with the homebound older adult population; and monitoring the participant-volunteer relationship through volunteer-completed reports to mitigate issues. Findings from this formative evaluation provide insight on strategies CBOs can employ to overcome challenges associated with implementing technology training programs to reduce social isolation and loneliness for older adults, and thus improve overall wellbeing for homebound older adults. Recommendations can be integrated into program design to facilitate implementation of ICT programs in the community setting.